Implementation and Application of Automata 26th International Conference, CIAA 2022, Rouen, France, June 28 - July 1, 2022, Proceedings - Caron, Pascal; Mignot, Ludovic (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book constitutes the proceedings of the 26th International Conference on Implementation and Application of Automata, CIAA 2022, held in Rouen, France in June/ July 2022. The 16 regular papers presented together with 3 invited lectures in this book were carefully reviewed and selected from 26 submissions. The topics of the papers covering various fields in the application, implementation, and theory of automata and related structures.
On 25 Years of CIAA Through the Lens of Data Science -- Manipulation of Regular Expressions Using Derivatives: an Overview -- How to Settle the ReDoS Problem: Back to the Classical Automata Theory -- Ordered Context-Free Grammars -- Symbolic Weighted Language Models, Quantitative Parsing and Automated Music Transcription -- A Similarity Measure for Formal Languages Based on Convergent Geometric Series -- Hybrid Tree Automata and the Yield Theorem for Constituent Tree Automata -- Some results concerning careful synchronization of partial automata and subset synchronization of DFA's -- A Toolkit for Parikh Matrices -- Syntax Checking Either Way -- On the Power of Pushing or Stationary Moves for Input-Driven Pushdown Automata -- The Cut Operation in Subclasses of Convex Languages (Extended Abstract) -- Variations of the Separating Words Problem -- Homomorphisms on graph-walking automata -- Nondeterministic State Complexity of Site-Directed Deletion -- Energy Complexity of Regular Language Recognition -- Real-Time, Constant-Space, Constant-Randomness Verifiers -- Constrained Synchronization for Monotonic, Solvable and Automata with Simple Idempotents -- An Ambiguity Hierarchy of Weighted Context-free Grammars.
Keywords: Natural language processing (Computer science).; Database management; Software engineering; Computer science; Machine theory; Logic programming; Natural Language Processing (NLP).; Database Management; Software Engineering; Computer Science Logic and Foundations of Programming; Formal Languages and Automata Theory; Logic in AI